CRIMINAL LIABILITY FOR CYBER THEFT IN THE CRIMINAL CODE OF THE REPUBLIC OF UZBEKISTAN: ANALYSIS OF EXISTING NORMS AND PROSPECTS FOR IMPROVEMENT (TAMADDUN NURI JURNALI, 2025)
As the Republic of Uzbekistan rapidly implements digital transformation, cybersecurity threats, including the problem of cyber-theft, are becoming increasingly relevant. This article aims to assess the current state of liability for cyber-theft in the Criminal Code of the Republic of Uzbekistan. It analyzes existing legal norms, identifies gaps and shortcomings in legislation, and proposes directions for improvement based on international experience. The article aims to contribute to Uzbekistan's efforts in ensuring security in the digital space and developing a sustainable digital economy.